Characterization of microRNAs from Arabidopsis galls highlights a role for miR159 in the plant response to the root‐knot nematode Meloidogyne incognita. Issue 3 (14th September 2017) - Medina, Clémence; da Rocha, Martine; Magliano, Marc; Ratpopoulo, Alizée; Revel, Benoît; Marteu, Nathalie; Magnone, Virginie; Lebrigand, Kevin; Cabrera, Javier; Barcala, Marta; Silva, Ana Cláudia; Millar, Anthony; et al.
Summary: Root knot nematodes (RKN) are root parasites that induce the genetic reprogramming of vascular cells into giant feeding cells and the development of root galls. MicroRNAs (miRNAs) regulate gene expression during development and plant responses to various stresses. Disruption of post‐transcriptional gene silencing in Arabidopsis ago1 or ago2 mutants decrease the infection rate of RKN suggesting a role for this mechanism in the plant‐nematode interaction. By sequencing small RNAs from uninfected Arabidopsis roots and from galls 7 and 14 d post infection with Meloidogyne incognita, we identified 24 miRNAs differentially expressed in gall as putative regulators of gall development. Moreover, strong activity within galls was detected for five miRNA promoters. Analyses of nematode development in an Arabidopsis miR159abc mutant had a lower susceptibility to RKN, suggesting a role for the miR159 family in the plant response to M. incognita . Localization of mature miR159 within the giant and surrounding cells suggested a role in giant cell and gall. Finally, overexpression of miR159 in galls at 14 d post inoculation was associated with the repression of the miR159 target MYB33 which expression is restricted to the early stages of infection. Overall, these results implicate the miR159 in plant responses to RKN.